Discrepant Results of Flexible Endoscopic Evaluation of Swallowing (FEES) and Videofluoroscopy Swallowing Study (VFSS) in Myasthenia Gravis’ Patient - Tamin, Susyana; Octavia, Devianty (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Myasthenia gravis (MG) is an autoimmune neuromuscular disorder that causes weakness in skeletal muscles. Dysphagia is an early symptom that is often found in 6-15% of patients with myasthenia gravis. Flexible Endoscopic Evaluation of Swallowing (FEES) and Video Fluoroscopic Swallowing Study (VFSS) examinations are routinely used to diagnose dysphagia. This paper reports a case of Male, 51 years old diagnosed with neurogenic oropharyngeal dysphagia due to MG. Swallowing evaluation post-therapy and rehabilitation programs were carried out. Interestingly both FEES and VFSS had a significant discrepant result. In cases of dysphagia due to MG, when interpreting objective swallowing function examination, confounding factors such as fatigue, timing of examinations, and time of taking medication specifically anticholinesterase (Pyridostigmine), should be taken into consideration.